Protein Kinase CK2 Regulates B-cell Development and Differentiation - Wei, Hairong (J Immunol, 2021)
Protein kinase CK2 (also known as Casein Kinase 2) is a serine/threonine kinase composed of two catalytic subunits (CK2α and/or CK2α’) and two regulatory CK2β subunits. CK2 is overexpressed and overactive in B-cell acute lymphoblastic leukemia and diffuse large B-cell lymphomas, leading to inappropriate activation of the NF-κB, JAK/STAT and PI3K/AKT/mTOR signaling pathways and tumor growth. However, whether CK2 regulates normal B-cell development and differentiation is not known. We generated mice lacking CK2α specifically in B-cells (using CD19-driven Cre recombinase). These mice exhibited cell-intrinsic expansion of marginal zone B (MZB) cells at the expense of transitional B (TrB) cells, without changes in follicular B (FoB) cells. TrB cells required CK2α to maintain adequate B-cell receptor (BCR) signaling. In the absence of CK2α, reduced BCR signaling and elevated Notch2 signaling activation increased MZB cell differentiation. Our results identify a previously unrecognized function for CK2α in B-cell development and differentiation.